Can the Prerequisites for Diffusion of Innovations Be Enhanced in a Local Government? - A case study of Lerum’s local government in Sweden - Bertling, Emelie; Brattberg, Klara (My University, 2017)
Innovation has been a field of studies where the focus on the private sector has been prominent. However, in recent years, the interest for public sector innovation has increased. In addition, also the field of diffusion of innovation has gained increased attention, but with limited studies within the context of a local government. The purpose of this study is to contribute to the understanding of the work with innovations in the public sector by addressing what factors that affect the diffusion of innovation in a local government, and how the prerequisites for diffusion can be enhanced by an improved implementation process. In order to fulfil the purpose, data has been collected at Lerum’s local government in terms of two interview rounds and a conducted survey. The empirical findings were analysed together with the reviewed literature concerning diffusion of innovation theory, implementation theory as well as theory regarding public sector innovation. The study resulted in one conceptual model illustrating the diffusion of innovations and one guide for implementation being of a more practical character. The diffusion model includes an innovation-decision process, where individuals and their adoption process are affected by a number of factors both within and outside the organisation. The communication is also seen as one integrated and important part of this process. The implementation guide highlights areas being recommended for practitioners to take into account in order to improve the implementation process and thereby also the prerequisites for diffusion of innovation. After the development of the model and the guide, they were validated by a group of local experts and after this, revised in order to fit the operations of Lerum’s local government. The result of this study will be valuable for Lerum’s local government as well as other local governments.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics